Constrângerea fizică şi psihică în cadrul actelor/acţiunilor sexuale neconsimţite - Galan, Doina-Cezara (CEP USM, 2024)
The conditions of victims sexual consent, presents both theoretical and practical interest. It was used the analytical, comparative and logical method to analyze the conditions that the consent of the victim may present in the case of the inviolability of sexual life. The aim of this study is to elucidate some aspects of physical and mental coercion according this kind of crimes.
FIZICAL AND PHYSICAL COERCION IN THE CONTEXT OF SEXUAL ACTS/ACTIONS WITHOUT CONSENT
Keywords: consent; physical restraint; mental restraint